Spatial distribution and characteristics of injecting drug users (IDU) in five Northeastern states of India - Sarathy Kalpana; Liegise Buno; Akoijam Brogen S; Adhikary Rajatashuvra; Mahanta Jagadish; Medhi Gajendra; Thomas Chelliah; Sarmah Bhupen (BMC, 2011)
Abstract Background Injecting drugs is the major driving force of human immunodeficiency virus (HIV) epidemic in Northeastern India. We have assessed the spatial distribution of locations where injecting drug users (IDU) congregate, as well as the risk behaviour and key characteristics of IDUs to develop new strategies strengthening intervention measures for HIV prevention in this region. Methods Locations of IDUs congregation for buying and injecting drugs were identified through Key Informants (KI). Verification of the location and its characteristics were confirmed through field visits. We also conducted semi-structured and structured interviews with IDUs to learn more about their injecting behaviour and other characteristics. Results Altogether, 2462 IDU locations were identified in 5 states. The number of IDU locations was found to be greater in the states bordering Myanmar. Private houses, parks, abandoned buildings, pharmacies, graveyards, and isolated places were the most frequently chosen place for injecting drugs. Many injecting locations were visited by IDUs of varying ages, of which about 10-20% of locations were for females. In some locations, female IDUs were also involved in sex work. Sharing of needle and syringes was reported in all the states by large proportion of IDUs, mainly with close friends. However, even sharing with strangers was not uncommon. Needle and syringes were mainly procured from pharmacies, drug peddlers and friends. Lack of access to free sterile needles and syringes, and inconsistent supplies from intervention programs, were often given as the cause of sharing or re-use of needles and syringes by IDUs. Most of the IDUs described a negative attitude of the community towards them. Conclusion We highlight the injection of drugs as a problem in 5 Northeastern India states where this is the major driving force of an HIV epidemic. Also highlighted are the large numbers of females that are unrecognized as IDUs and the association between drug use and sex work. Understanding of risk behaviours and other key charecteristics of IDUs in the region will help in strengthening harm reduction efforts that can prevent HIV transmission.